A conservative surgical approach of osteochondroma affecting the mandibular condyle - Rivera, Helen; Bastidas, Ramiro; Acevedo, Ana María (Investigación Clínica, 2013)
An osteochondroma of the condyle in a 49-year-old Venezuelan female patients Is reported. Clinical, radiological and histopathological features of the tumor are described. A wide local surgical excision permitted the patient to regain normal function.